Educational and labour trajectories of the young children of immigrants in Spain - Labrador Fernández, Jesús; Blanco Puga, María Rosa (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This article presents a study on the integration of the young adult and adolescent children of immigrants into the educational system and the labor market. It examines the impact of various factors on this integration process, including social capital, family history and educational background, gender, and school resources. Intensive interviews have been conducted with a sample of Moroccan, Chinese, and Dominican immigrants between 16 and 24 years of age and the analysis explores their discourse with respect to their educational trajectory (finished or unfinished) and their past and current work experiences. The findings indicate that a number of factors play a role in this process as well as in the ability of the subjects to make the transition to adulthood. Some of the most important amongst them are: age on arrival, gender, family involvement in and support for the daily schoolwork of their children and the attitudes and autonomy of the children with regard to the decisions they make about their future
Keywords: Immigration; Children of immigrants; Educational trajectories; Transition to adulthood